Redukcja wyrazów podobnych. mam na jutro



Redukcja Wyrazów Podobnych Mam Na Jutro class=

Odpowiedź :

a) 2a + (4a - 3b + 5c) + (5c - 2b) = 2a + 4a - 3b + 5c + 5c - 2b = 6a - 3b + 10c

6 × 1 - 3 × 2 + 10 × 3 = 6 - 6 + 10 = 10

b) 5x + 3y + ( 2y - 4z) - (5y + 6z) = 5x + 3y +2y - 4z - 5y - 6z = 5x - 10z

c) -3r - (2r - 4s - t) - (6r + 5s) = -3r - 2r + 4s + t - 6r - 5s = - 11r - 1s + t

d) 4k - (2m + n) - (- k - m) + (3m - n) = 4k - 2m - n - k + m + 3m - n = 3k + 2m - 2n

e) 5m + 3n - 5 - ( 2m - 3n - 5) = 5m + 3n - 5 - 2m + 3n + 5 = 3m + 6n

f)  3 - (4a - 6b) + (2 - a - 7b) = 3 - 4a + 6b + 2 - a - 7b = 5 - 5a - b

5 - 5 × 1 - 2 = - 2

g) - 2c + 4 - (3c + 2d) - ( 5d - 2) = - 2c + 4 - 3c - 2d - 5d + 2 = - 5c + 6 - 7d

- 5 × 3 + 6 - 7 × 4 = - 15 + 6 - 28 = - 9 - 28 = - 37

h) 8p - (3 - 4p - r) - (2 + 3p + 5r) = 8p - 3 + 4p + r - 2 - 3p - 5r = 9p - 5 + p

Inne Pytanie